Rangamandapa, Mukhamandapa and Garbhagriha of the Ghateshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The Ghateshwar Temple consists of a garbhagriha (sanctum sanctorum), antarala (vestibule or antechamber) and a mukhamandapa (front porch) on plan. There is a rangamandapa (an open type of pillared hall used for ceremonial rituals) in front of the temple on the same axis. Both mandapas (pillared hall) feature a phamsana shikhara (pyramidal superstructure) while the garbhagriha has a latina shikhara (mono-spired superstructure).